2012
DOI: 10.1007/s11606-012-2045-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient–Provider Discussions about Colorectal Cancer Screening: Who Initiates Elements of Informed Decision Making?

Abstract: BACKGROUND: Colorectal cancer (CRC) screening rates remain low among low-income minority populations. OBJECTIVE: To evaluate informed decision making (IDM) elements about CRC screening among low-income minority patients. DESIGN: Observational data were collected as part of a patient-level randomized controlled trial to improve CRC screening rates. Medical visits (November 2007 to May 2010) were audio-taped and coded for IDM elements about CRC screening. Near the end of the study one provider refused recording … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…In particular, similar to what has been found in previous studies, 8,[13][14][15] we found that there was a significant lack of effort to elicit patients' perspectives (knowledge, concerns, values, preferences), which is a critical component of shared decision making. [9][10][11] Given that more than 90% of physician participants self-reported that they usually took their patients' preferences into account when making treatment decisions (compared with only about 20% who explicitly told the standardized patient that decisions should be based on the patient's values and preferences), there may be a large gap between (1) the physicians' perception of or belief in their communication skill and their actual communication behavior, and (2) between the physicians' assumption of their patients' perspectives and their patients' actual perspectives.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In particular, similar to what has been found in previous studies, 8,[13][14][15] we found that there was a significant lack of effort to elicit patients' perspectives (knowledge, concerns, values, preferences), which is a critical component of shared decision making. [9][10][11] Given that more than 90% of physician participants self-reported that they usually took their patients' preferences into account when making treatment decisions (compared with only about 20% who explicitly told the standardized patient that decisions should be based on the patient's values and preferences), there may be a large gap between (1) the physicians' perception of or belief in their communication skill and their actual communication behavior, and (2) between the physicians' assumption of their patients' perspectives and their patients' actual perspectives.…”
Section: Discussionsupporting
confidence: 88%
“…6 In general, existing literature suggests that shared decision making requires that physicians engage in 3 broad groups of behaviors during consultations regarding PSA testing: (1) provision of information, ie, provision of balanced and evidence-based information regarding prostate cancer and prostate cancer screening options, including potential harms and benefits of each option; (2) elicitation of the patient's perspective, ie, assessing a patient's wish to be actively involved in decision making, asking about his prior experience, and eliciting his concerns about prostate cancer, as well as his values and preferences regarding different screening options; and (3) guiding final decision making, ie, providing guidance without being overly directive. [7][8][9][10][11] Even though physicians typically report that they engage in shared decision making about cancer screening, patients commonly deny having any such discussion with their physician. [12][13][14][15] To understand how the physician approached discussions of risk and uncertainty around prostate cancer screening, we undertook a transcript analysis of standardized patient clinic encounters, examining (1) which elements of shared decision making occurred when physicians were prompted to discuss prostate cancer screening, (2) whether intervention physicians engaged in more behaviors related to the 3 elements of shared decision making, and (3) whether intervention physicians were more neutral than control physicians in their final recommendations for screening and ordering PSA screening tests.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, screening behavior was not evaluated [26]. In a recent study, researchers found that CRC screening was mentioned in 48% of the primary care visits; however, in almost half of those visits, no additional discussion of CRC screening occurred [25]. One-third of those visits included both a discussion of CRC screening and an assessment of the patient’s understanding of CRC screening [25].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, researchers found that CRC screening was mentioned in 48% of the primary care visits; however, in almost half of those visits, no additional discussion of CRC screening occurred [25]. One-third of those visits included both a discussion of CRC screening and an assessment of the patient’s understanding of CRC screening [25]. However, only 6% of those CRC screening discussions included assessment of patient test preferences; therefore low levels of IDM were found [25].…”
Section: Introductionmentioning
confidence: 99%
“…Missed opportunities to engage in shared decision making also emerge in the paper by Katz et al,6 who showed that even when patients were activated to discuss CRC screening, the topic came up in just 48 of 100 visits, and there was no further discussion in 23 of those 48 visits. Finally, the article by Shah et al…”
mentioning
confidence: 99%